Peran Lembaga Anti Korupsi Indonesia dalam Mendukung Program Pemerintah Memberantas Korupsi di Kabupaten Karo - Aulia, Nadira Debi; Sinaga, Rudi Salam (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
Corruption is a serious challenge in governance in Indonesia, including in Karo Regency. LAKRI plays a role in supervision, legal advocacy, and anti-corruption education to increase transparency and accountability in the regions. This study aims to analyze the role of LAKRI in eradicating corruption in Karo Regency, identify the challenges faced, and explore strategies that can be carried out to improve the effectiveness of anti-corruption supervision and advocacy. The research method used is qualitative with a descriptive approach, where data is obtained through in-depth interviews, observations, and documentation. The results of the study show that the main obstacles faced by LAKRI include limited resources, political pressure and intimidation, low community participation, and lack of coordination with law enforcement officials. To overcome these obstacles, a strategy is needed that includes strengthening resources, legal protection for activists, increasing community participation, and optimizing cooperation with law enforcement. With wider support, LAKRI is expected to carry out its role more effectively in creating a clean and transparent local government.